Agricultural Land-Use Classification on Satellite Data Using Machine Learning - Nguyen Thao-Ngan; Nguyen Van-Ho (Business Systems Research)
The utilization of satellite images has become increasingly popular for detecting land usage, focusing on agricultural land classification in recent years, due to the significant decline in bees.